2021
DOI: 10.1007/s00068-021-01618-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep infection following reconstruction of pelvic fractures: prevalence, characteristics, and predisposing risk factors

Abstract: Purpose To identify the incidence, risk factors, and treatment course of patients who developed deep infection following fixation of pelvic fractures. Methods Over a period of 8 years patients who underwent pelvic reconstruction in our institution and developed postoperative infection were included. Exclusion criteria were pathological fractures and infections that were not secondary to post-traumatic reconstruction. The mean time of follow-up was 43.6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
2
13
1
Order By: Relevance
“…The treatment strategy for infectious complications after pelvic ring stabilization requires an individual approach and good interdisciplinary cooperation as guidelines based on prospective clinical trials are still lacking. In terms of cohort sizes, our study is comparable with two recent studies also devoted to pelvic infections: Bakhshayesh et al 2018 [2] and Kanakaris et al 2021 [10]. Bakhshayesh et al reported a similar proportion of reoperations for surgical site infections as in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The treatment strategy for infectious complications after pelvic ring stabilization requires an individual approach and good interdisciplinary cooperation as guidelines based on prospective clinical trials are still lacking. In terms of cohort sizes, our study is comparable with two recent studies also devoted to pelvic infections: Bakhshayesh et al 2018 [2] and Kanakaris et al 2021 [10]. Bakhshayesh et al reported a similar proportion of reoperations for surgical site infections as in our study.…”
Section: Discussionsupporting
confidence: 91%
“…However, in contrast with our study, a post hoc analysis on sex-based subgroups was not performed [2]. In Kanakaris et al's study, a larger number of risk factors were investigated, logistic regression was used for the analysis rather than Cox regression, and in their multivariate analysis ISS score, diabetes, a posterior approach, and alcohol abuse were all identified as independent risk factors [10]. Other studies focused on fewer risk factors than our study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The small sample size, the retrospective nature of the study, the relative short-term follow-up and combination of acute fractures with malunited cases are the main ones. On considering that pelvic fractures make up approximately 3% of all fractures, and that prevalence of surgical site infection following fixation of pelvic ring injury is 2.1% [3] , this disastrous complication fortunately represents a rare occurrence. This limits collection of an adequate sample in a single center.…”
Section: Article In Pressmentioning
confidence: 99%
“…Definitive operative intervention usually requires extensive surgical approaches, massive soft tissue dissection and lengthy procedures [2] . The prevalence of surgical site infection following fixation of pelvic ring injury is 2.1% [3] . The immunosuppressive state induced by trauma, open extremity associated injuries, massive blood loss, intensive care admission predispose to both local and systemic infections.…”
Section: Introductionmentioning
confidence: 99%